VOLATILITY ANALYSIS OF INDONESIA COMPOSITE INDEX DURING COVID-19 - Catur Kumala Dewi; Rina Masithoh Haryadi (Universitas Muhammadiyah Kalimantan Timur, 2021)
Concerns over Covid-19 hit global financial markets, indicating that during the period of Covid-19 spread, financial markets experienced high uncertainty, from fluctuating tendencies several times to declining and difficult to control. At the beginning of the pandemic, Indonesia's capital market conditions were worse than during the 2008 crisis. At the end of March 2020, JCI was far behind 3,938. IDX and OJK conduct various stock policies so that the Indonesian capital market and JCI recover. The study aims to calculate and analyze differences in the volatility of JCI before and during Covid-19 in Indonesia. The data analysis method used is paired with a simple t-test using R Studio as a calculation tool. The results showed that there was a significant difference in the volatility of JCI before and during Covid-19 in Indonesia.